STUDI KOMPARATIF EVALUASI PENEMPATAN PEDAGANG KAKI LIMA PASCA RELOKASI: STUDI KOMPARATIF EVALUASI PENEMPATAN PEDAGANG KAKI LIMA PASCA RELOKASI - Annisa Ullya Rahma (Ide dan Dialog Desain Indonesia (Idealog), 2026)
Abstract : The increasing demand for public spaces has led to significant socio-economic changes, including the relocation of street vendors (PKL) to restore the function of public areas. However, this relocation often presents challenges for PKL. In 2023, PKL in Bandung were moved to Basement Alun-Alun Bandung and Level 1 Griya Buah Batu, while in 2022, PKL in Yogyakarta were relocated to Teras Malioboro 1 and 2. This study aims to evaluate the impact of these relocations, focusing on their positive and negative outcomes from the perspective of PKL as the most affected group. A design approach was employed by combining qualitative and quantitative methods. Data were collected through observations, interviews, and questionnaires, then analyzed using public space theory and public policy evaluation criteria. The study assesses three key parameters: space quality, accessibility, and the suitability of the location for PKL businesses. The findings indicate that Teras Malioboro 1 offers the best facilities and comfort, while Griya Buah Batu and Basement Alun-Alun Bandung are less adequate in terms of design and functionality. Despite differences between locations, all PKL experienced a decline in income due to low visibility in the relocation areas and increased distance from customers. This study concludes that while improved space quality enhances comfort, strategic visibility and accessibility remain crucial factors for the sustainability of PKL businesses. Future relocations must balance space improvements with these factors to ensure both economic and functional success. Keywords : Comparative Study, Street Vendors, City Square, Visibility, Circulation.